Socio-economic impacts of Gorai riverbank erosion on people: a case study of Kumarkhali, Kushtia - Baki, A.T.M. Abdullahel (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.